Tunnel-type β-FeOOH cathode material for high rate sodium storage via a new conversion reaction. (November 2017) - Cho, Min Kyoung; Jo, Jae Hyeon; Choi, Ji Ung; Kim, Jongsoon; Yashiro, Hitoshi; Yuan, Shuai; Shi, Liyi; Sun, Yang-Kook; Myung, Seung-Taek
Abstract: We have investigated a tunnel-type β-FeOOH cathode material for rapid sodium storage. Rietveld refinement of the X-ray diffraction (XRD) data obtained for β-FeOOH indicated that the structure was stabilized into [2 × 2] hollandite tunnel structure, and the adhesion of the β-FeOOH onto carbon nanotubes (CNTs) led to a high electrical conductivity of 3 S cm −1 . As a result, the β-FeOOH/CNTs composite electrode showed excellent electrode performance, with a discharge capacity of 205 mAh g −1 and a coulombic efficiency of 88.5% in the voltage range of 1.1–4 V during the first cycle, 131 mAh g −1 after 200 cycles, and a capacity retention of 70% over 300 cycles at 10 C (1920 mA g −1 ). Based on the XRD, X-ray absorption, and time-of-flight secondary-ion mass spectroscopy results, we suggest a new conversion mechanism for the β-FeOOH cathode material in Na cells, namely, FeOOH + Na + + e - → FeO + NaOH. This conversion reaction produces NaOH as a byproduct, and the reaction is fairly reversible even at 10 C-rates. Graphical abstract: We report on tunnel type β-FeOOH nano-stick particles embedded in carbon nanotubes. The β-FeOOH/CNTs composite represents rapid sodium storage capability via a new conversion reaction, which is fairly reversible at high rates for a long term. Highlights: β-FeOOH/CNTs composite is suggested as an cathode material for Na-ion batteries. β-FeOOH/CNTs composite is activated by a new conversion reaction via Fe 3+/2+ redox. β-FeOOH/CNTs composite shows a high electric conductivity, 3 S cm −1 . β-FeOOH/CNTs composite is fairly reversible at high rates for a long term.